Household listing and farm household baseline surveys for the food security and agribusiness support (FAS) activity and improving maternal and child health nutrition services (IMCHN) activity - International Food Policy Research Institute (United States Agency for International Development, 2019)
This baseline report is part of a project funded by the United States Agency for International Development (USAID) and implemented by the International Food Policy Research Institute (IFPRI) to evaluate the Feed the Future Egypt, Food-Security and Agribusiness Support (FAS) and the Improving Maternal and Child Health and Nutrition Services (IMCHN) projects. The evaluations of FAS and IMCHN are conducted in two main phases: (1) the baseline study, and (2) the evaluation study. This report presents the results of the baseline study. For the baseline study, IFPRI in collaboration with El-Zanaty and Associates conducted a household listing survey from March 29th to April 2nd, 2018 followed by a farm household baseline survey from April 9th to May 8th, 2018 in six Upper Egypt governorates (Assiut, Beni Suef, Luxor, Menya, Qena, and Sohag). A total of 40 enumerators, 10 technicians (for the collection of anthropometry data within the Farm Household Survey) and 10 supervisors were involved in the data collection. Data for both surveys was collected using Computer Assisted Personal Interview (CAPI) technology. This baseline report summarizes the findings of both surveys. The results of the listing survey analysis serve to inform USAID about farm households’ project participation and treatment by FAS and IMCHN, in addition to establishing the sampling frame for the baseline study. The results of the farm household baseline survey analysis determine the baseline indicator values against which FAS and IMCHN will be evaluated in Phase 2. In addition, the analysis of the farm household baseline survey provides new evidence that can help to improve policy and program design and implementation to better leveraging agriculture-health-nutrition linkages in Upper Egypt.